Boron delivery for boron neutron capture therapy targeting a cancer-upregulated oligopeptide transporter - Junji Miyabe; Ryuichi Ohgaki; Keijiro Saito; Ling Wei; Lili Quan; Chunhuan Jin; Xingming Liu; Suguru Okuda; Shushi Nagamori; Hiroshi Ohki; Kazuo Yoshino; Hidenori Inohara; et al. (Elsevier, 2019)
Boron neutron capture therapy (BNCT) is a radiotherapy utilizing the neutron capture and nuclear fission reaction of 10B taken up into tumor cells. The most commonly used boron agent in BNCT, p-borono-l-phenylalanine (BPA), is accumulated in tumors by amino acid transporters upregulated in tumor cells. Here, by using dipeptides of BPA and tyrosine (BPA-Tyr and Tyr-BPA), we propose a novel strategy of selective boron delivery into tumor cells via oligopeptide transporter PEPT1 upregulated in various cancers. Kinetic analyses indicated that BPA-Tyr and Tyr-BPA are transported by oligopeptide transporters, PEPT1 and PEPT2. The intrinsic oligopeptide transport activity in tumor cells clearly correlated with PEPT1 protein expression level but not with PEPT2, suggesting that PEPT1 is the predominant oligopeptide transporter at least in tumor cell lines. Furthermore, using BPA-Tyr and Tyr-BPA, boron was successfully delivered into PEPT1-expressing pancreatic cancer AsPC-1 cells via a PEPT1-mediated mechanism. Intravenous administration of BPA-Tyr into the mice bearing AsPC-1 xenograft tumors resulted in significant boron accumulation in the tumors. It is proposed that the oligopeptide transporters, especially PEPT1, are promising candidates for molecular targets of boron delivery in BNCT. The BPA-containing dipeptides would have a potential for the development of novel boron carriers targeting PEPT1. Keywords: Boron delivery, Boron neutron capture therapy, p-Borono-l-phenylalanine-containing dipeptide, Oligopeptide transporter, PEPT1